Perception and Appreciation: The Wiwit Kopi Tradition in Carangwulung Village, Wonosalam District, Jombang - Putra Pangestu , Rachmat Karunia; Indah, Novita Kartika (LenteraBio : Berkala Ilmiah Biologi, 2023)
Carangwulung Village, Wonosalam Sub-district, Jombang is a village in East Java that has a coffee commodity. The cultivated coffee plants are closely related to the local knowledge of the community, thus creating local wisdom in the form of the wiwit kopi tradition. The tradition originates from the community’s perception and appreciation of coffee plants, so this study aims to determine the level of community perception in the coffee wiwit tradition and community appreciation of coffee plants. The research used a descriptive method. Data were obtained through interviews using questionnaires and through open-ended questions. The research participants were 65 people selected by purposive sampling from each hamlet in Carangwulung Village. Data were analyzed quantitatively using a Likert scale and perception and appreciation formulas to calculate the percentage of questionnaire answers. The results showed that the participants’ local knowledge was different, with young people having percentages in the range of less to sufficient while the elderly had a range of good to very good. This is shown as the perception of young age is sufficient on the meaning of tradition at 53.13% compared to the elderly age is very good at 88.75%, and the appreciation of young age is sufficient such as conservation 59.38% while the elderly age is very good at 85%.